2019
DOI: 10.22454/fammed.2019.743181
|View full text |Cite
|
Sign up to set email alerts
|

Essential Skills for Family Medicine Residents Practicing Integrated Behavioral Health

Abstract: Background and Objectives: There are several trends compelling physicians to acquire team-based skills for interprofessional care. One underdeveloped area of team-based skills for physicians is integrated behavioral health (IBH) in primary care. We used a Delphi method to explore what skills were needed for residents to practice integrated behavioral health. Methods: We conducted a literature review of IBH competencies and found 41 competencies across seven domains unique to physicians. Using a modified Delphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…20 This finding is consistent with literature identifying communication and teamwork as critical competencies for physicians working in integrated behavioral health. 11 Future research may explore these links more directly, and could inform critical interventions for this population. When exploring how PCBH content was delivered, findings suggested that while disease-specific processes may often be taught in a didactic fashion, the majority of integrated care specific content was delivered through practice based placements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 This finding is consistent with literature identifying communication and teamwork as critical competencies for physicians working in integrated behavioral health. 11 Future research may explore these links more directly, and could inform critical interventions for this population. When exploring how PCBH content was delivered, findings suggested that while disease-specific processes may often be taught in a didactic fashion, the majority of integrated care specific content was delivered through practice based placements.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Accreditation Council for Graduate Medical Education (ACGME) Milestones recognize the critical role behavioral health plays in family medicine, and behavioral faculty are a mainstay of residency training programs, 12 there is little systematic understanding of training in integrated behavioral health service delivery models. 11,13 A recent scoping review identified that while a large number of training programs in family medicine, internal medicine, and pediatrics include interprofessional training in behavioral health, there is little formal identification of service delivery models or intentional curriculum on health care team integration. 13 This is a critical gap, as education and shared goals are key aspects of building successful health care teams.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most common were behavioural health clinicians specialising in mental health conditions, including psychologists, social workers and medical practitioners. Other groups were leaders [20,21], managers [21], primary care professionals [22], expert clinicians [23][24][25][26][27], healthcare students [5], medical graduates [23,28], physicians [29], social service providers in the community [26], health and social care workers or behavioural health providers [29][30][31][32] and educators and academics [23,20]. For example, one study described an integrated care training programme for social workers alongside community social service providers [26].…”
Section: Target Workforcementioning
confidence: 99%
“…Featured in this issue of Family Medicine is an important article about the integration of behavioral health and primary care. 3 In this paper, Matt Martin, PhD, and colleagues have described how they used a Delphi process and focus groups to identify a list of essential competencies for family medicine residents to master before entering practices with integrated behavioral health teams. The methods used in this study are rigorous and the results are of broad importance to all family medicine educators.…”
Section: From the Editormentioning
confidence: 99%